Detecting discrete spatial heterogeneity in compositional data via generalized group minimax concave penalty regularization - Ryo Inoue; Masato Ishikawa; Zhan Peng (Spatial Statistics, 2026)

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Detection of three novel loci involved in reduced seed-shattering behaviour of an aus rice cultivar, Oryza sativa Kasalath - Naoki Shionari; Yudai Yamaguchi; Natsumi Takama; Yumi Oka; Yoshiaki Takenaka; Naohiro Matsubara; Chizuru Inoue; Than Myint Htun; Yuki Tsujimura; Koji Numaguchi; Takashige Ishii; Ryo Ishikawa (Molecular Genetics and Genomics, 2025)

Thyroid Hormone (T3) Induces Male-like Reproductive Behavior in Female Tilapia - Taiga Midorikawa; Ryo Kaneko; Sakura Inoue; Atsuhiro Tsutiya; Ritsuko Ohtani-Kaneko (Fishes, 2025)
In most vertebrates, males and females display distinct reproductive behaviors. Some fish can change their sexual phenotype at various life stages, which involves alterations in their gonadal sex and changes in their reproductive behavior to align with the new gonadal identity. Although the sex reversal phenomenon in reproductive behavior is well documented, the underlying mechanisms in the brains of these fish remain largely unknown. In the present study, we investigated the roles of the thyroid hormone (triiodothyronine (T3)) in the Mozambique tilapia as a potential regulator of male-specific nest-building behavior and gonadotropin-releasing hormone-3 (GnRH3) neurons, the regulatory neurons of male reproductive behavior, in the terminal nerve (TN) ganglion. T3 injection successfully induced nest-building behavior in mature female fish. T3 injection significantly elevated serum T3 concentrations in treated animals compared with those in controls. Through organotypic culture of brain slices that included the TN region, we demonstrated that T3 could stimulate an increase in the number of GnRH3 neurons, and the effect was inhibited by a thyroid hormone receptor (TR) inhibitor. Additionally, TRβ co-expression was observed in GnRH3 neurons. These findings highlight the crucial roles of T3 and GnRH3 in sex reversal processes within the fish brain.

Changes in the coastal environments and their impact on society in the Qaanaaq region, northwestern Greenland - Shin Sugiyama; Atsushi Yamaguchi; Tatsuya Watanabe; Yasumasa Tojo; Naotaka Hayashi; Jean-Baptiste Thiebot; Makoto Tomiyasu; Kohei Hasegawa; Yoko Mitani; Mayuko Otsuki; Yuta Sakuragi; Monica Ogawa; et al. (Polar Science, 2025)

Intestinal D-amino acids content is highly related to intestinal IgA production upon soluble dietary fiber ingestion in mice - Kenji Matsumoto; Ayaka Noguchi; Funa Miyamoto; Ryo Inoue; Hirokazu Hirai; Tomohiro Miwa; Yoshinori Nakagawa; Yasuki Higashimura (Food Chemistry, 2025)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Anthropogenic gadolinium contamination assessment in sewage, river, and tap water samples from the urban Osaka area, Japan - Kazumasa Inoue; Thennaarassan Natarajan; Ryo Isoda; Masahiro Fukushi; Sarata Kumar Sahoo (Science of The Total Environment, 2025)

Hepatocyte nuclear factor 4α is a critical factor for the production of complement components in the liver - Carlos Ichiro Kasano-Camones; Satomi Yokota; Maiko Ohashi; Noriaki Sakamoto; Daichi Ito; Yoshifumi Saito; Ryo Uchida; Kazumi Ninomiya; Yusuke Inoue (In Vitro Cellular & Developmental Biology - Animal, 2024)

Changes in fecal microbiota during estrous cycle in healthy thoroughbred mares - Junjie Li; Haruka Toyama; Touko Matsumoto; Mohammad Ibrahim Qasimi; Ryo Inoue; Harutaka Murase; Yuki Yamamoto; Kentaro Nagaoka (Journal of Equine Veterinary Science, 2024)

Correction: Detection of novel loci involved in non-seed-shattering behaviour of an indica rice cultivar, Oryza sativa IR36 - Shohei Sugiyama; Motoki Sakuta; Yuki Tsujimura; Yudai Yamaguchi; Than Myint Htun; Chizuru Inoue; Koji Numaguchi; Takashige Ishii; Ryo Ishikawa (Molecular Genetics and Genomics, 2023)

Detection of novel loci involved in non-seed-shattering behaviour of an indica rice cultivar, Oryza sativa IR36 - Shohei Sugiyama; Motoki Sakuta; Yuki Tsujimura; Yudai Yamaguchi; Than Myint Htun; Chizuru Inoue; Koji Numaguchi; Takashige Ishii; Ryo Ishikawa (Molecular Genetics and Genomics, 2023)
Asian rice ( Oryza sativa ) was domesticated from O. rufipogon , and reduced seed-shattering behaviour was selected to increase yields. Two seed-shattering loci, qSH3 and sh4 , are involved in reducing seed shattering in both japonica and indica rice cultivars, while qSH1 and qCSS3 are likely specific to japonica cultivars. In indica cultivars, qSH3 and sh4 fail to explain the degree of seed shattering, as an introgression line (IL) of O. rufipogon W630 carrying domesticated alleles at qSH3 and sh4 still showed seed shattering. Here we analysed differences in seed-shattering degree between the IL and the indica cultivar IR36. The values for grain detachment in the segregating population between the IL and IR36 were continuous. Based on QTL-seq analysis using the BC 1 F 2 population between the IL and IR36, we detected two novel loci, qCSS2 and qCSS7 ( QTLs for the Control of Seed Shattering in rice on chromosomes 2 and 7 ), which contributed to the reduced seed shattering in IR36. We further investigated the genetic interaction of qCSS2 and qCSS7 under the presence of qSH3 and sh4 mutations in O. rufipogon W630 and found that IL carrying IR36 chromosomal segments covering all four loci are required to explain seed-shattering degree in IR36. Since qCSS2 and qCSS7 were not detected in previous studies on seed shattering in japonica , their control may be specific to indica cultivars. Therefore, they are important to understanding the history of rice domestication as well as to adjusting the seed-shattering degree of indica cultivars to maximise their yield.

Robustness of the Mean Flow Similarity in an Urban Roughness Sublayer to Different Inflow Properties - Atsushi Inagaki; Ryo Inoue; Manabu Kanda; Yasuaki Mori (Boundary-Layer Meteorology, 2023)

Therapeutic angiogenesis for patients with no-option critical limb ischemia by adipose-derived regenerative cells: TACT-ADRC multicenter trial - Yuuki Shimizu; Kazuhisa Kondo; Ryo Hayashida; Ken-ichiro Sasaki; Masanori Ohtsuka; Yoshihiro Fukumoto; Shinichiro Takashima; Oto Inoue; Soichiro Usui; Masayuki Takamura; Masashi Sakuma; Teruo Inoue; et al. (Angiogenesis, 2022)

Two Hidden mtDNA-Clades of Crown-of-Thorns Starfish in the Pacific Ocean - Nina Yasuda; Jun Inoue; Michael R. Hall; Manoj R. Nair; Mehdi Adjeroud; Miguel D. Fortes; Mutsumi Nishida; Nat Tuivavalagi; Rachel Ravago-Gotanco; Zac H. Forsman; Taha Soliman; Ryo Koyanagi; et al. (Frontiers in Marine Science, 2022)
Recurring outbreaks of crown-of-thorns starfish (COTS) severely damage healthy corals, especially in the Western Pacific Ocean. To obtain a better understanding of population genetics of COTS and historical colonization across the Pacific Ocean, complete mitochondrial genomes were sequenced from 243 individuals collected in 11 reef regions. Our results indicate that Pacific COTS ( Acanthaster cf. solaris ) comprise two major clades, an East-Central Pacific (ECP) clade and a Pan-Pacific (PP) clade, separation of which was supported by high bootstrap value. The ECP clade consists of COTS from French Polynesia, Fiji, Vanuatu and the Great Barrier Reef (GBR). The Hawaii population is unique within this clade, while California COTS are included in EPC clade. On the other hand, the PP clade comprises multiple lineages that contain COTS from Vietnam, the Philippines, Japan, Papua New Guinea, Micronesia, the Marshall Islands, GBR, Vanuatu, Fiji and French Polynesia. For example, a lineage of the PP clade, which has the largest geographic distribution, includes COTS from all of these locations. These results suggest two alternative histories of current geographic distributions of COTS in the Pacific Ocean, an ECP clade ancestry or Western Pacific clade ancestry. Although further questions remain to be explored, this discovery provides an evolutionary context for the interpretation of COTS population structure which will aid future coral reef research in the Pacific Ocean, and ultimately improve reef management of COTS.

Sleep Apnea Syndrome (SAS) Clinical Practice Guidelines 2020 - Tsuneto Akashiba; Yuichi Inoue; Naohisa Uchimura; Motoharu Ohi; Takatoshi Kasai; Fusae Kawana; Shigeru Sakurai; Misa Takegami; Ryo Tachikawa; Takeshi Tanigawa; Shintaro Chiba; Kazuo Chin; et al. (Sleep and Biological Rhythms, 2022)
The prevalence of sleep-disordered breathing (SDB) is reportedly very high. Among SDBs, the incidence of obstructive sleep apnea (OSA) is higher than previously believed, with patients having moderate-to-severe OSA accounting for approximately 20% of adult males and 10% of postmenopausal women not only in Western countries but also in Eastern countries, including Japan. Since 1998, when health insurance coverage became available, the number of patients using continuous positive airway pressure (CPAP) therapy for sleep apnea has increased sharply, with the number of patients about to exceed 500,000 in Japan. Although the “Guidelines for Diagnosis and Treatment of Sleep Apnea Syndrome (SAS) in Adults” was published in 2005, a new guideline was prepared to indicate the standard medical care based on the latest trends, as supervised by and in cooperation with the Japanese Respiratory Society and the “Survey and Research on Refractory Respiratory Diseases and Pulmonary Hypertension” Group, of Ministry of Health, Labor and Welfare and other related academic societies, including the Japanese Society of Sleep Research, in addition to referring to the previous guidelines. Since sleep apnea is an interdisciplinary field covering many areas, this guideline was prepared including 36 clinical questions (CQs). In the English version, therapies and managements for SAS, which were written from CQ16 to 36, were shown. The Japanese version was published in July 2020 and permitted as well as published as one of the Medical Information Network Distribution Service (Minds) clinical practice guidelines in Japan in July 2021.

Effects of saffron and its constituents, crocin-1, crocin-2, and crocetin on α-synuclein fibrils - Eiji Inoue; Yasuharu Shimizu; Ryo Masui; Tomomi Hayakawa; Tomoe Tsubonoya; Satoko Hori; Keiichi Sudoh (Journal of Natural Medicines, 2018)

Estimation of loci involved in non-shattering of seeds in early rice domestication - Ryo Ishikawa; Akinori Nishimura; Than Myint Htun; Ryo Nishioka; Yumi Oka; Yuki Tsujimura; Chizuru Inoue; Takashige Ishii (Genetica, 2017)

Assessment of soil remediation technologies by comparing health risk reduction and potential impacts using unified index, disability-adjusted life years - Iwao Sakaguchi; Yasushi Inoue; Shinichiro Nakamura; Yoshihiro Kojima; Ryo Sasai; Kayo Sawada; Kenji Suzuki; Chisato Takenaka; Arata Katayama (Clean Technologies and Environmental Policy, 2015)

Development of Meloxicam Salts with Improved Dissolution and Pharmacokinetic Behaviors in Rats with Impaired Gastric Motility - Masanori Ochi; Ryo Inoue; Yukinori Yamauchi; Shizuo Yamada; Satomi Onoue (Pharmaceutical Research, 2013)

Combined Use of In Vitro Phototoxic Assessments and Cassette Dosing Pharmacokinetic Study for Phototoxicity Characterization of Fluoroquinolones - Yoshiki Seto; Ryo Inoue; Masanori Ochi; Graham Gandy; Shizuo Yamada; Satomi Onoue (The AAPS Journal, 2011)

Gene Expression Patterns in the Outer Mantle Epithelial Cells Associated with Pearl Sac Formation - Nariaki Inoue; Ryo Ishibashi; Takashi Ishikawa; Takashi Atsumi; Hideo Aoki; Akira Komaru (Marine Biotechnology, 2011)

Can the Quality of Pearls from the Japanese Pearl Oyster (Pinctada fucata) be Explained by the Gene Expression Patterns of the Major Shell Matrix Proteins in the Pearl Sac? - Nariaki Inoue; Ryo Ishibashi; Takashi Ishikawa; Takashi Atsumi; Hideo Aoki; Akira Komaru (Marine Biotechnology, 2011)

Comparative expression of hexose transporters (SGLT1, GLUT1, GLUT2 and GLUT5) throughout the mouse gastrointestinal tract - Tohru Yoshikawa; Ryo Inoue; Megumi Matsumoto; Takaji Yajima; Kazunari Ushida; Toshihiko Iwanaga (Histochemistry and Cell Biology, 2011)

Hypomethylation and transcriptional reactivation of retrotransposon-like sequences in ddm1 transgenic plants of Brassica rapa - Ryo Fujimoto; Taku Sasaki; Hisashi Inoue; Takeshi Nishio (Plant Molecular Biology, 2008)

Development and implementation of a database system to manage a large-scale mouse ENU-mutagenesis program - Hiroshi Masuya; Yuji Nakai; Hiromi Motegi; Norio Niinaya; Yuichiro Kida; Yoshiharu Kaneko; Haruhiko Aritake; Nobuaki Suzuki; Jun Ishii; Koji Koorikawa; Tomohiro Suzuki; Maki Inoue; et al. (Mammalian Genome, 2004)